2019
DOI: 10.1002/apj.2334
|View full text |Cite
|
Sign up to set email alerts
|

Foam fractionation for enhancing silica gel adsorption of urokinase from human urine

Abstract: In this work, foam fractionation (FF), a cost-effective method, was used to enhance the silica gel adsorption (SGA) of urokinase from human urine. The analysis of how FF enhanced the adsorption/desorption of urokinase onto silica gel was conducted. The results show that FF increased both the adsorption rate of urokinase onto silica gel and the activity concentration of urokinase adsorbed at silica gel by pre-enriching urokinase from urine. It also reduced the activity loss of urokinase in the desorption proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In a study, as an example, 27% ± 8% of thrombus was dissolved by streptokinase, while 64% ± 9% of an equivalent thrombus sample was dissolved by urokinase within the same time frame of 60 minutes (Ouriel, 2002). A recent study falls in agreement, stating that streptokinase partially consumes plasminogen (and plasmin) while forming the activator complex, whereas urokinase converts all of the plasminogen to plasmin, making it more efficient (Xu et al, 2019). Furthermore, for the local thrombolytic therapy, improved efficacy of lysis and a decreased percentage of systemic fibrinolytic effect and bleeding problems make urokinase preferable over streptokinase again (Tan et al, 2017).…”
Section: Efficacymentioning
confidence: 87%
See 2 more Smart Citations
“…In a study, as an example, 27% ± 8% of thrombus was dissolved by streptokinase, while 64% ± 9% of an equivalent thrombus sample was dissolved by urokinase within the same time frame of 60 minutes (Ouriel, 2002). A recent study falls in agreement, stating that streptokinase partially consumes plasminogen (and plasmin) while forming the activator complex, whereas urokinase converts all of the plasminogen to plasmin, making it more efficient (Xu et al, 2019). Furthermore, for the local thrombolytic therapy, improved efficacy of lysis and a decreased percentage of systemic fibrinolytic effect and bleeding problems make urokinase preferable over streptokinase again (Tan et al, 2017).…”
Section: Efficacymentioning
confidence: 87%
“…According to a study (Dubey et al, 2011), a five to six-fold increase in purity was observed by first performing column chromatography and then column electrophoresis in sucrose density gradients. In a likewise study, Xu et al, (2019) obtained a final specific activity of 100,000 units of streptokinase per mg of protein by coupling ion-exchange and gel-permeation chromatography.…”
Section: Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of foam separation was evaluated by protein recovery (R p ) [9], the protein enrichment ratio (E p ) [14], enzyme recovery (R e ) [32], Enzyme activity enrichment ratio (E e ) [12] and puri cation ratio (P f ) [32], which are calculated as following formula:…”
Section: Evaluation Of Foam Separation Effectmentioning
confidence: 99%
“…The two most critical factors for foam separation e ciency are surface adsorption and foam drainage [10]. The enhanced foam drainage is recognized as an effective way to improve the enrichment ratio [11,12]. By adjusting the system properties of the solution (such as temperature, pH, etc.…”
Section: Introductionmentioning
confidence: 99%